ANALYSIS OF RESULTS OF RESEARCH OF INTERACTION OF INSTITUTIONS OF GENERAL SECONDARY AND OUT-OF-SCHOOLS EDUCATION IN AESTHETIC EDUCATION OF TEENAGERS - Sierykh Larisa Vladimirovna (International Journal of Innovative Technologies in Social Science, 2020)
The article reveals the main results of scientific research on the implementation of the system of interaction of general secondary and out-of-school education institutions in the aesthetic education of teenagers. Methods of diagnosing the aesthetic education of students at the stages of the ascertaining and formative stages of the study, which were used during the experiments, confirmed the need and correctness of the conclusions. The main purpose of improving the aesthetic education of adolescents - the integration of the existing system and new forms of interaction, event technology in education as a technology of impressions and a component of the system of socio-pedagogical activities in educational institutions, methods of interaction, and methods of aesthetic education aimed at creative activities, promotes acme success, creative self-realization of teenagers. As a result of introduction of multi-vector model the tendencies of development of aesthetic education of modern teenagers in the conditions of application of system of interaction of establishments of general secondary and out-of-school education in aesthetic education of teenagers are allocated. A general trend for both control and experimental groups is a decrease in the number of teenagers who show a "low" level of aesthetic education. This allows us to argue about the feasibility of the proposed system of interaction of general secondary and out-of-school education in the aesthetic education of teenagers, the introduction of new forms, methods of interaction in the practice of school and out-of-school. With such interaction, the out-of-school education institution is able to solve a range of tasks aimed at aesthetic education of teenagers in particular and humanization of general secondary education in general: integrate resources of out-of-school and general secondary education, equalize initial opportunities at the same time to each pupil acme success, to promote self-realization of the personality of the child and the teacher.